Once again “the Scythian” myth of origins (Herodotus 4.5–10) - Bruce Lincoln (Nordlit: Tidsskrift i litteratur og kultur, 2014)
Far from being authorless texts, eternal truths, and the authentic voice of the Volk (as Romantic theories have it), myths are narratives that disguise both their authorship and their tendentious nature. The two variants of “the” Scythian origin myth preserved in Herodotus 4.5–6 and 4.8–10 provide a convenient example of how close reading permits one to identify the interests advanced by each variant through the ways they rework details of the structure they have in common.